2021
DOI: 10.3389/fmicb.2021.762263
|View full text |Cite
|
Sign up to set email alerts
|

One Health Approaches to Trace Mycobacterium leprae’s Zoonotic Potential Through Time

Abstract: Hansen’s disease (leprosy), mainly caused by infection with Mycobacterium leprae, has accompanied humanity for thousands of years. Although currently rare in Europe, there are over 200,000 new infections annually in South East Asia, Africa, and South America. Over the years many disciplines – palaeopathology, ancient DNA and other ancient biomolecules, and history – have contributed to a better understanding of leprosy’s past, in particular its history in medieval Europe. We discuss their contributions and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Studies have also revealed significant diversity of strains through time and coupled with studies of modern strains in both humans and animals, the clear interchange of these pathogens from humans to other species and back again (e.g., refs. 107 and 109 111 ). These mycobacteria are also among the first where we can see evidence for genetic susceptibility of particular subsets of ancient populations.…”
Section: Pathogen Genomicsmentioning
confidence: 99%
“…Studies have also revealed significant diversity of strains through time and coupled with studies of modern strains in both humans and animals, the clear interchange of these pathogens from humans to other species and back again (e.g., refs. 107 and 109 111 ). These mycobacteria are also among the first where we can see evidence for genetic susceptibility of particular subsets of ancient populations.…”
Section: Pathogen Genomicsmentioning
confidence: 99%
“…One Health has been defined by the World Health Organisation as an integrated, unifying approach to balance and optimize the health of people, animals and ecosystems (WHO, 2022). Past research into deep-time perspectives on One Health has sometimes focused on specific infectious diseases, such as brucellosis or leprosy (Bendrey et al, 2020;Urban et al, 2021), while others have attempted a broad theoretical overview of how zoonoses and environment might have interacted from a One Health perspective in past era (Kim and Agarwal, 2023;Rayfield et al, 2023). The study of health and disease in past populations is termed paleopathology (Gauer, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Archaeologists can help address this problem by documenting the deeper history of humans in shaping diseases. However, archaeological methods, tools and data have not fully been leveraged in One Health approaches, with a few notable exceptions such as the One Health Archaeology Research Group at the University of Edinburgh and a handful of initiatives and researchers elsewhere [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%